PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE DAN SERVICE FEATURES TERHADAP MINAT GENERASI Z DALAM PENGGUNAAN E-WALLET DI KOTA AMBON - Kevin Tamaela; Linda Grace Loupatty; Yuyun Yuniarti Layn (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
The purpose of this study was to empirically examine the effect of perceived usefulness, perceived ease of use, and service features on generation z's interest in using e-wallets in Ambon City. This research is descriptive quantitative research, which was conducted in the city of ambon using the population is generation z who are studying at the Faculty of Economics and Business, Pattimura University. The research sample amounted to 124 people who were students majoring in Accounting, Faculty of Economics and Business, Pattimura University who used the e-wallet digital payment system. The study used primary data obtained using survey data collection techniques using a questionnaire distributed online with google form. The data analysis method uses multiple linear regression statistical analysis. The results showed that perceived usefulness, perceived ease of use, and service features have a positive and significant effect on generation z's interest in using e-wallets in ambon city.